Aspect Ratio of PEGylated Upconversion Nanocrystals Affects the Cellular Uptake In Vitro and In Vivo. (15th July 2022) - Fu, Libing; Shi, Bingyang; Wen, Shihui; Morsch, Marco; Wang, Guoying; Zhou, Zhiguang; Mi, Chao; Sadraeian, Mohammad; Lin, Gungun; Lu, Yiqing; Jin, Dayong; Chung, Roger
Abstract: The central nervous system (CNS) is protected by the blood-brain barrier (BBB), which acts as a physical barrier to regulate and prevent the uptake of endogenous metabolites and xenobiotics. However, the BBB prevents most non-lipophilic drugs from reaching the CNS following systematic administration. Therefore, there is considerable interest in identifying drug carriers that can maintain the biostability of therapeutic molecules and target their transport across the BBB. In this regard, upconversion nanoparticles (UCNPs) have become popular as a nanoparticle-based solution to this problem, with the additional benefit that they display unique properties for in vivo visualization. The majority of studies to date have explored basic spherical UCNPs for drug delivery applications. However, the biophysical properties of UCNPs, cell uptake and BBB transport have not been thoroughly investigated. In this study, we described a one-pot seed-mediated approach to precisely control longitudinal growth to produce bright UCNPs with various aspect ratios. We have systematically evaluated the effects of the physical aspect ratios and PEGylation of UCNPs on cellular uptake in different cell lines and an in vivo zebrafish model. We found that PEGylated the original UCNPs can enhance their biostability and cell uptake capacity. We identify an optimal aspect ratio for UCNP uptake into several different types of cultured cells, finding that this is generally in the ratio of 2 (length/width). This data provides a crucial clue for further optimizing UCNPs as a drug carrier to deliver therapeutic agents into the CNS. Statement of significance: The central nervous system (CNS) is protected by the blood-brain barrier (BBB), which acts as a highly selective semipermeable barrier of endothelial cells to regulate and prevent the uptake of toxins and pathogens. However, the BBB prevents most non-lipophilic drugs from reaching the CNS following systematic administration. The proposed research is significant because identifying the aspect ratio of drug carriers that maintains the biostability of therapeutic molecules and targets their transport across the blood-brain barrier (BBB) is crucial for designing an efficient drug delivery system. Therefore, this research provides a vital clue for further optimizing UCNPs as drug carriers to deliver therapeutic molecules into the brain. Graphical abstract: Image, graphical abstract